2023
DOI: 10.3390/jcm12237358
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Preterm Birth among Secundiparas with a Previous Cesarean due to a Failed Vacuum Delivery

Sarit Helman,
Muhammad Mahajna,
Zvi Ehrlich
et al.

Abstract: Background: Studies have found an association between second-stage cesarean sections (SSCSs) and subsequent preterm birth (PTB). We aimed to evaluate if secundiparas with previous second-stage cesarean sections due to a failed vacuum delivery (SSCS-F-VD) are associated with PTB in the subsequent delivery compared with secundiparas with previous spontaneous vaginal birth (SVB) at term. A secondary aim was to compare this association with secundiparas with a previous SSCS at term. Methods: A historical, prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…It is important to highlight that the present study has identified a positive association between an SSCD following a failed vacuum to a low-segment uterine segment extension. This observation aligns with a previous study conducted by our group, which reported a positive association between an SSCD following a failed vacuum and PTB [11]. Stratifying the groups of CDs by the occurrence of a low-segment uterine incisional extension did not show an association between secundiparas with a history of SSCD with extension compared with secundiparas without uterine extensions, RR 2.3 (CI 0.6; 8.4, p = 0.218).…”
Section: Referencesupporting
confidence: 90%
See 3 more Smart Citations
“…It is important to highlight that the present study has identified a positive association between an SSCD following a failed vacuum to a low-segment uterine segment extension. This observation aligns with a previous study conducted by our group, which reported a positive association between an SSCD following a failed vacuum and PTB [11]. Stratifying the groups of CDs by the occurrence of a low-segment uterine incisional extension did not show an association between secundiparas with a history of SSCD with extension compared with secundiparas without uterine extensions, RR 2.3 (CI 0.6; 8.4, p = 0.218).…”
Section: Referencesupporting
confidence: 90%
“…Previous studies searched for an association between SSCD and PTB based on the understanding that SSCD is associated with low-segment uterine incisional extension and that uterine extensions can cause mechanical injury to the cervix, possibly leading to cervical incompetence and PTB [3][4][5][6][7]11,16,[18][19][20]. Some found a positive association [4,5,18,19,21] and others did not find an association [7,16,20,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Study population : The obstetric characteristics of the study population are extensively described [ 9 ]. In summary, annually, SZMC conducts around 14,500 deliveries, with approximately 25% of cases being nulliparous, ~18% classified as grand multiparous (parity ≥ 6), ~12% involving CD, and ~5% utilizing vacuum deliveries.…”
Section: Methodsmentioning
confidence: 99%